Observational Study of the Multisciplinaryteam role (MDT) on Healthcare Management of Cancer Patients: Benefits and Barriers, AbuDhabi 2017 - Al Obaidi, Ibtisam Hussein (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Multidisciplinary team meetings (MDTs) are designed to optimize patient outcomes. It appears intuitive that MDTs are essential to clinical decision - making and patient management; however, it is unclear whether that belief is supported by evidence. With regard to cancer patients, studies demonstrated that treatment plans made by interacting health care professionals are more effective than those made by individual practitioners. Objectives: To assess the impact of multidisciplinary teams (MDTs) on clinical decision - making and patient outcomes. Methods: We follow a descriptive questionnaire survey study design and created a (10) sections surveymonkey that was distributed via email to (150) experts in surgical oncology, general surgery, oncology, radiation oncology, pathologists, and administrative staff. Fourty (40) completed responses were collected to ensure a statistical basis on which to draw sound conclusions. The remaining 110 staff have submitted incomplete answers. Answers were discussed in a separate MDT meeting with most of the participants.The survey was followed by an interpretation of the respondents’ results and comparison with literatures. Results: 75% of the participants chose” Agree and strongly agree”, supporting the hypothesis that MDT meetings ensure an effective and up-to- date management guidelines. This means that the risk of not discussing a cancer patient cannot be neglected any longer. So the hypothesis statement (H0) is rejected and the alternative statement (Ha) is accepted. Conclusions: The majority of participants saw the value in the MDT process and expressed support for its implementation locally and nationally; however, feedback about the most appropriate format is yet to be established. The clinicians identified the need for agreed standards in MDT performance